Becoming a Mother During the Covid-19 Pandemic in Serbia - Vlajić, Milica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
The aim of this exploratory qualitative research is to interpret the effects of the crisis caused by the COVID-19 pandemic on the experience of becoming a mother. The subjective experience of the transition to motherhood is shaped in relation to experiences within certain stages which include decision to give birth, pregnancy, childbirth, period immediately after the birth of a child and period of early motherhood, but it is also constructed in relation to discourses on "good motherhood" and its displaying, as well as the perception of informal and institutional support. The COVID-19 pandemic has produced new challenges to individuals and groups in almost every segment of human existence, so we start from the hypothesis that the effects of the crisis had an enormous impact on the experience of becoming a mother. The participants in this research were ten first-time mothers who gave birth in the period between March 2020 and February 2021. Results indicate that the context of the pandemic significantly influenced the experience of transition to motherhood in each of its phases.